Effectiveness of Automation in Evaluating Test Results Using EvalBee as an Alternative Optical Mark Recognition (OMR): A Quantitative-Evaluative Approach from a Philippine Public School (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
AbstractWithin this study, the authors want to address the problem of overworking of teachers in Philippine schools due to their excessive clerical responsibility, which could lead to teacher attrition. The authors propose to automate the process, particularly the evaluation of student test results since it could improve human well-being by reducing the burden of manual labor. Automation using OMR has not been widely applied in Philippine schools due to cost issues. The authors want to observe whether an alternative OMR - EvalBee - can meet the evaluation standard even though it is free of charge. The study employed a quantitative-evaluative research method. Validated questionnaires on paper and a Google Form survey were used to collect relevant data in a secondary public school in the City Schools Division of Cabuyao – Southville1 Integrated National High School. Statistical tools such as the mean, standard deviation, t-test, and Cohen's d were used in this research to determine the effectiveness of using alternative OMR in evaluating examinations. This study shows that alternative OMR is efficient, accurate, and reliable, despite the fact that it is free, and recommends it be used as part of the teachers' standard method of test evaluation.